2021
DOI: 10.3390/su13148101
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Long-Term Care in Jamaica: Addressing an Ageing Population

Abstract: Jamaica’s ageing population, high prevalence of non-communicable diseases (NCDs), and associated functional impairments suggest the need for a sustainable long-term care (LTC) system. This paper describes the current LTC system in Jamaica. A review of empirical and grey literature on LTC was supplemented with consultations and interviews and group discussions for knowledge exchange, impact and engagement events with stakeholders being conducted as part of a project on dementia care improvement. Four key findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Responses to limited services. Formal dementia carer support services are minimal in Jamaica, but participants noted that before the pandemic more general psycho-social supports were available, provided by church groups and non-governmental organizations, geared towards stress management (Govia et al, 2021). Following the shift to remote service provision, eight participants from the middle to upper SES classification, noted that they were able to continue to access social supports virtually or, more importantly, access new supports they could not access pre-pandemic due to the in-person time commitments or their immobility.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Responses to limited services. Formal dementia carer support services are minimal in Jamaica, but participants noted that before the pandemic more general psycho-social supports were available, provided by church groups and non-governmental organizations, geared towards stress management (Govia et al, 2021). Following the shift to remote service provision, eight participants from the middle to upper SES classification, noted that they were able to continue to access social supports virtually or, more importantly, access new supports they could not access pre-pandemic due to the in-person time commitments or their immobility.…”
Section: Resultsmentioning
confidence: 99%
“…Before the onset of the COVID-19 pandemic, unpaid carers constructed tailored, informal care systems with the resources available to them. In the context of Jamaica, these care systems existed despite a lack of dementia-specific social safety nets (Govia et al, 2021). While the construction of these informal care systems is commendable, the pandemic has emphasized their fragility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Jamaica, social care services and social protection mechanisms are not integrated with health care and so there is a lesser likelihood of vulnerable group members being “visible” in the health and social care system in a coordinated manner and with continuity of care. In the context of some families being reliant on agencies and organizations that offer residential or boarding arrangements for vulnerable persons, COVID-19 closures and social contact restrictions have significantly increased demands on family members with already limited capacity to offer the needed care (Govia et al, 2021; Vigo et al, 2020). In this context, coordination of efforts with the limited resources is key, and especially coordinated efforts that facilitate changes in the systems of care and services available for these vulnerable group members (Vieira et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that some effects of vulnerable status may emerge over time; that vulnerability is not a static but a dynamic and multifaceted state (Govia et al, 2021;Smith & Judd, 2020). The pandemic has been of an extended duration and its effects will be long term.…”
Section: Vulnerable Groups In Jamaicamentioning
confidence: 99%